Internalized Weight Bias and Disordered Eating: The Mediating Role of Body Image Avoidance and Drive for Thinness - Marshall, Rachel D.; Latner, Janet D.; Masuda, Akihiko (Frontiers in Psychology, 2020)
Internalized weight bias has been linked with undesirable physical and psychological health outcomes, including disordered eating. Interventions have targeted internalized weight bias and associated outcomes, but little is known about underlying mechanisms of change. Existing treatment literature suggests that drive for thinness and body image avoidance may sustain the link between internalized weight bias and disordered eating. The present study aimed to determine if drive for thinness and body image avoidance mediated the relationship between internalized weight bias and disordered eating in an ethnically diverse sample. Participants included 225 female college students aged 18-49 years (mean age = 20.4 years, SD = 4.4), with a mean BMI of 23.3 kg/m2 who completed a computer-based survey for partial course credit. As expected, internalized weight bias was positively associated with disordered eating, and results supported the hypothesis of the mediating role of drive for thinness and body image avoidance. These results are important given the shortage of intervention efforts targeting internalized weight bias. Future intervention efforts aimed at reducing internalized weight bias and associated outcomes may benefit from simultaneously targeting drive for thinness and body image avoidance.